Analyzing job advertisements and skill descriptions using NLP techniques (part 1: data cleaning and pre-processing and part 4: front-end visualization/user interface) - collaboration with CAO - Dinglasan, Cris Anthony Sarmiento (Nanyang Technological University, 2024)
In a competitive job market, it is imperative that people continuously stay relevant to employers. This is especially important for fresh graduates with minimal working experience, and for workers in sunsetting industries, such as traditional print media and Landline telephone services. Efforts have been made by the Government of Singapore to facilitate this upskilling and reskilling amongst Singaporeans through their support of the SkillsFuture Movement.